Optical coherence tomography-defined vulnerable plaque characteristics in relation to functional severity of coronary stenoses stratified by quantitative flow ratio. (14th October 2021) - Zuo, W; Sun, R; Zhang, X; Qu, Y; Ji, Z; Su, Y; Zhang, R; Ma, G
Abstract: Background: The functional severity and morphological features of epicardial lesions are both related to plaque vulnerability and adverse coronary events. However, their relationship remains controversial, especially in patients with non-ST-segment elevation acute coronary syndrome (NSTE-ACS). Purpose: This study aimed to examine whether quantitative flow ratio (QFR), an angiography-based computation of fractional flow reserve, was associated with optical coherence tomography (OCT)-defined vulnerable plaques such as thin-cap fibroatheromas (TCFAs) in a board spectrum of population, including patients presenting stable angina and NSTE-ACS. Methods: We identified patients who underwent OCT examinations from 2 prospective cohorts and then assessed interrogated vessels with QFR. Lesions were divided into tertiles: QFR-T1 (QFR <0.85)<qfr), >, QFR-T2 (0.85 to 0.93) and QFR-T3 (QFR >0.93). Results: This post-hoc analysis included 83 lesions from 79 patients (mean age: 61.5±9.8 years, males: 58%). Patients with NSTE-ACS accounted for the majority of the population (67%). The median % diameter stenosis and median QFR value were 42% (36 to 49%) and 0.88 (0.83 to 0.95), respectively. The prevalence of OCT-TCFA was significantly higher in QFR-T1 (50%) than in QFR-T2 (14%) and QFR-T3 (19%) (p=0.003 and 0.018, respectively). Overall significant differences were observed among tertiles in maximum lipid arc, thinnest fibrous cap thickness (FCT), and minimal lumen area (MLA) (p=0.017, 0.040, and <0.001, respectively). The Spearman's correlation analysis showed that QFR was significantly related to MLA (ρ = 0.537, p<0.001), % area stenosis (ρ = –0.512, p<0.001), maximum lipid arc (ρ = –0.360, p=0.002), lipid length (ρ = –0.242, p=0.038), lipid index (ρ = –0.333, p=0.004), and thinnest FCT (ρ = 0.315, p=0.006). In the multivariable analysis, QFR ≤0.80 remained as a significant determinant of TCFAs regardless of the presence of NSTE-ACS and the level of low-density lipoprotein cholesterol (adjusted odds ratio = 4.387, 95% confidence interval: 1.297 to 14.839, p=0.017). In addition, QFR demonstrated moderate predictive ability for OCT-TCFA (area under the curve = 0.72, 95% confidence interval: 0.58 to 0.86, p=0.003) with the best cutoff of ≤0.86 (sensitivity: 65%; specificity: 73%; negative predictive value: 85%; accuracy: 71%). Conclusions: Lower QFR was related to OCT-TCFA and other vulnerable plaque characteristics in angiographically mild-to-intermediate stable lesions and culprit lesions from NSTE-ACS. The QFR might be a useful tool for ruling out high-risk, rupture-prone plaques without using any pressure wires or vasodilators. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): The Jiangsu Provincial Key Research and Development Program